Water Playing Method to Improve Science in Group B Children at PAUD Khairul Ummah - Selly Amalia; Juli Yanti Harahap (International Journal of Educational Research Excellence (IJERE), 2022)
This type of research is a quantitative research (experimental) with a one-group pretest-posttest design research method. The number of samples in this study amounted to 15 children with a population of 35 children. Based on the results of research conducted with normality testing and t-test, the results obtained are, normality testing using the Lilliefors method is obtained with the results of the data in the pre-test obtained the value of L table with determination = 0.05 with a sample size of 15 which is 0.220 then L count < L table (0.103 < 0.220) this indicates that the pre-test data is normally distributed. And in the post-test data obtained the value of L count < L table ( 0.170 < 0.220) this indicates that the post-test sample is normally distributed. And the calculation of the hypothesis test above can be seen and the t -value = 4.914 and the real level = 0.05 so that the t - table is 1.761. It can be concluded that t count > t table = 4.914 > 1.761, thus Ho is rejected and Ha is accepted. It is stated that there is a significant effect on the use of the water play method to improve the science of group B children in Khairul Ummah PAUD, Medan Johor district, for the 2021/2022 academic year.